Empowering Sharia-based MSMEs and financial institutions to enhance the halal industry ecosystem‎ - Arianty, Erny; Marsono, Marsono; Indrawati, Iin; Risnandar, Risnandar (Universitas Islam Indonesia, 2025)
IntroductionIndonesia has considerable potential to become a global leader in the halal industry, supported by its large Muslim population, thriving micro, small, and medium enterprises, and expanding Islamic financial institutions. However, the country still struggles to translate this potential into competitive advantage. Challenges persist in halal product certification, Sharia-compliant financing, regulatory alignment, and digital integration.ObjectivesThis study aims to identify key strategies for strengthening the halal industry ecosystem by optimizing the roles of micro, small, and medium enterprises and Islamic financial institutions. It seeks to analyze the most urgent problems and prioritize strategic interventions to support national competitiveness in the global halal market.MethodA qualitative approach combining thematic analysis and the Analytical Hierarchy Process was used. Data were collected through in-depth interviews with representatives from micro, small, and medium enterprises, Islamic financial service institutions, government agencies, and academics. Thematic analysis identified core challenges and potential strategies, which were then ranked using the Analytical Hierarchy Process to determine their relative importance.ResultsThe findings reveal that the most pressing challenges include complex halal certification processes, limited awareness of international halal standards among business actors, inadequate digital readiness, and regulatory barriers that hinder Islamic financing. The most important strategy identified was simplifying the halal certification process, followed closely by streamlining financing procedures in Islamic financial institutions. Regulatory support emerged as the most critical factor for strengthening the halal industry ecosystem, while strategies related to human resource development and financial access also played significant roles.ImplicationsThe results offer practical recommendations for policymakers, particularly in improving regulatory frameworks and enhancing financial inclusion for halal-oriented micro, small, and medium enterprises. For financial institutions, the study highlights the need for inclusive, accessible, and digitally integrated Sharia financing schemes to reach underserved business actors.Originality/NoveltyThis study presents a novel integration of qualitative insight and hierarchical decision modeling to evaluate the ecosystem of the halal industry in Indonesia. By prioritizing strategic issues and solutions, the research provides a structured roadmap for aligning micro, small, and medium enterprises with Islamic financial institutions under national development goals.